2004
DOI: 10.1212/01.wnl.0000146196.01316.a2
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in a novel ATP-dependent Lon protease gene in a kindred with mild mental retardation

Abstract: Background-Identifying the genetic factors that contribute to memory and learning is limited by the complexity of brain development and the lack of suitable human models for mild disorders of cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
179
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(184 citation statements)
references
References 29 publications
1
179
0
2
Order By: Relevance
“…6 Until now, 26 significantly linked non-specific intellectual disability of autosomal recessive inheritance (NS-ARID) loci were described, [7][8][9][10] and only 10 genes (six of them located in described regions) were identified: PRSS12 (OMIM#606709, on 4q26, former MRT1), CRBN (OMIM#609262, on 3p26, former MRT2), CC2D1A (OMIM#610055, on 19p13.12, former MRT3), ST3GAL3 (OMIM#606494, on 1p34.3), GRIK2 (OMIM#138277, on 6q16, former MRT6), TUSC3 (OMIM#601385, on 8p22, former MRT7), ZNF26 (no OMIM#, on 19q13.2), TRAPPC9 (OMIM#613192, on 8q24, former MRT13), ZCH14 (OMIM# 613279, on 14q31.3), and TECR (MIM*610057 on 19p13.12) (Figure 1). 1,[11][12][13][14][15][16][17][18][19] Taking into account that over 90 genes are responsible for only about 40% of X-chromosomal recessive ID cases, and that about half of the estimated 22 000 human genes are expressed in the brain, the total number of ARID genes may run into the hundreds. 1 Considering the heterogeneity observed in previous linkage studies, and the fact that the so far identified genes do not account for a significant fraction of NS-ARID cases, systematic approaches are the most promising strategy to identify further genes.…”
Section: Introductionmentioning
confidence: 99%
“…6 Until now, 26 significantly linked non-specific intellectual disability of autosomal recessive inheritance (NS-ARID) loci were described, [7][8][9][10] and only 10 genes (six of them located in described regions) were identified: PRSS12 (OMIM#606709, on 4q26, former MRT1), CRBN (OMIM#609262, on 3p26, former MRT2), CC2D1A (OMIM#610055, on 19p13.12, former MRT3), ST3GAL3 (OMIM#606494, on 1p34.3), GRIK2 (OMIM#138277, on 6q16, former MRT6), TUSC3 (OMIM#601385, on 8p22, former MRT7), ZNF26 (no OMIM#, on 19q13.2), TRAPPC9 (OMIM#613192, on 8q24, former MRT13), ZCH14 (OMIM# 613279, on 14q31.3), and TECR (MIM*610057 on 19p13.12) (Figure 1). 1,[11][12][13][14][15][16][17][18][19] Taking into account that over 90 genes are responsible for only about 40% of X-chromosomal recessive ID cases, and that about half of the estimated 22 000 human genes are expressed in the brain, the total number of ARID genes may run into the hundreds. 1 Considering the heterogeneity observed in previous linkage studies, and the fact that the so far identified genes do not account for a significant fraction of NS-ARID cases, systematic approaches are the most promising strategy to identify further genes.…”
Section: Introductionmentioning
confidence: 99%
“…5 -7 Only two autosomal genes, the PRSS12 gene on chromosome 4q26 [MIM 606709] and the CRBN gene on chromosome 3p26 [MIM 607417], have been shown to cause autosomal recessive NSMR, each gene in only one family. 8,9 Autosomal recessive diseases are common in the Arab population of Israel, mostly as a result of the high rate of consanguinity. Among Israeli Arabs, up to 44% of the marriages used to be between relatives, approximately half of which were between first cousins, although these numbers are somewhat lower today.…”
Section: Introductionmentioning
confidence: 99%
“…Cereblon (CRBN), 3 a gene on human chromosome 3p26.2, was initially reported as a candidate gene for a mild form of autosomal recessive non-syndromic mental retardation (ARNSMR) (1). Subsequently, the CRBN protein has been characterized in several different cellular contexts.…”
mentioning
confidence: 99%
“…Despite the significance of CBRN in brain function, suggested by clinical and experimental evidence (1,16), the molecular etiology of the cognitive phenotypes resulting from CRBN mutation has not been elucidated. In this study, we investigated the functional roles of CRBN as an upstream regulator of the mTOR signaling pathway.…”
mentioning
confidence: 99%